1999
DOI: 10.1016/s0169-328x(98)00323-4
|View full text |Cite
|
Sign up to set email alerts
|

The leukemic oncogene tal-2 is expressed in the developing mouse brain

Abstract: tal-1 (T-cell acute leukemia-1; also known as SCL) and tal-2 genes belong to a family of basic helix-loop-helix transcription factors and were originally isolated from the breakpoints of chromosomal translocations in human T-cell leukemia cell lines. tal-1 is expressed not only in hematopoietic cells but also in several endothelial structures and the central nervous system during development. On the other hand, the detailed function and the sites of expression of tal-2 have remained obscure. We cloned the tal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…It has been reported that Tal2 expression was observed in embryonic head (E10.5 to E14.5)10. We also confirmed Tal2 expression in embryogenesis (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It has been reported that Tal2 expression was observed in embryonic head (E10.5 to E14.5)10. We also confirmed Tal2 expression in embryogenesis (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Tal2 is expressed during embryogenesis, and sites of Tal2 expression include specific regions of the diencephalon, mesencephalon and metencephalon10. Tal2 -null mutant mice are viable at birth and initially appear normal.…”
mentioning
confidence: 99%
“…A radioactive DNA probe for OUT was prepared by randomprimed labeling of a 1.4-kb PstI-XbaI fragment of the OUT cDNA (nt 398 -1791). Hybridization and washing were performed under high stringency conditions as described previously (56). The full-length glyceraldehyde-3-phosphate dehydrogenase (GAPDH) cDNA was adopted as a probe for an internal loading control.…”
Section: Methodsmentioning
confidence: 99%
“…essentially as described previously (56). 35 S-Labeled antisense and sense riboprobes were prepared by in vitro transcription with suitable RNA polymerases following linearization of pCMV-OUT (see below) with appropriate restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation